INCIDENCE OF PREDIABETES AND DIABETES IN WOMEN WITH PREVIOUS GESTATIONAL DIABETES AND NON-ALCOHOLIC FATTY LIVER DISEASE: A PROSPECTIVE COHORT STUDY. - Behera, Rajesh Ranjan; Kumari, Manisha (Student's Journal of Health Research Africa, 2024)
Background Non-alcoholic fatty liver disease (NAFLD) and gestational diabetes mellitus (GDM) are two common metabolic disorders that have similar pathophysiological mechanisms, including chronic inflammation and resistance to insulin. The aim of this research was to examine the incidence of prediabetes and diabetes in females who had previously experienced GDM and NAFLD, and to determine the variables linked to the advancement of glycaemic categories within this cohort. Methods The study included 230 women who were evaluated for NAFLD at a baseline postpartum visit. The participants were categorized based on their GDM status during pregnancy and NAFLD presence. Incidence rates of prediabetes and diabetes were calculated, and significant predictors of glycaemic progression were identified. Data collection included medical history, anthropometric measurements, and biochemical parameters. Statistical analyses were performed using Stata 15.0. Results Of 230 women, 167 (72.6%) had GDM, and 63 (27.4%) had normoglycaemia during pregnancy. Over 3 years, 98 (42.6%) developed prediabetes or diabetes, with higher incidence rates in those with both GDM and NAFLD. Key factors for glycaemic progression were age >35 (OR 2.3, p=0.005), postpartum overweight/obesity (OR 3.1, p<0.001), family history of diabetes (OR 1.9, p=0.02), and NAFLD presence (OR 2.7, p=0.001). Cardiometabolic risk factors worsened significantly, especially in women with GDM and NAFLD. Conclusion Females with GDM and NAFLD are at high risk for prediabetes and diabetes. Glycaemic progression is predicted by age, postpartum BMI, family history of diabetes, and NAFLD. These findings suggest targeted surveillance and early intervention to avoid diabetes and manage cardiometabolic hazards in this high-risk group. Recommendations Regular screening for glycaemic status and cardiometabolic risk factors should be prioritized in females with a history of GDM and NAFLD. Lifestyle interventions focusing on weight management and metabolic health are essential to reduce the progression to prediabetes and diabetes in this high-risk group.